Melanin mitigates the accelerated decay of mycorrhizal necromass with peatland warming. (4th January 2019) - Fernandez, Christopher W.; Heckman, Katherine; Kolka, Randall; Kennedy, Peter G.
Abstract: Despite being a significant input into soil carbon pools of many high‐latitude ecosystems, little is known about the effects of climate change on the turnover of mycorrhizal fungal necromass. Here, we present results from the first experiment examining the effects of climate change on the long‐term decomposition of mycorrhizal necromass, utilising the Spruce and Peatland Response Under Changing Environments (SPRUCE) experiment. Warming significantly increased necromass decomposition rates but was strongest in normally submerged microsites where warming caused water table drawdown. Necromass chemistry exerted the strongest control on the decomposition, with initial nitrogen content strongly predicting early decay rates (3 months) and initial melanin content determining mass remaining after 2 years. Collectively, our results suggest that as global temperatures rise, variation in species biochemical traits as well as microsites where mycorrhizal necromass is deposited will determine how these important inputs contribute to the belowground storage of carbon in boreal peatlands.